2019
DOI: 10.3390/ijms20051049
|View full text |Cite
|
Sign up to set email alerts
|

CB2 Receptor Stimulation and Dexamethasone Restore the Anti-Inflammatory and Immune-Regulatory Properties of Mesenchymal Stromal Cells of Children with Immune Thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disorder characterized by antibody-mediated platelet destruction, with a complex and unclear pathogenesis. The impaired immunosuppressive capacity of mesenchymal stromal cells in ITP patients (ITP-MSCs) might play a role in the development of the disease. Correcting the MSC defects could represent an alternative therapeutic approach for ITP. High-dose dexamethasone (HD-Dexa) is the mainstay of the ITP therapeutic regimen, although it has several side effects. We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(43 citation statements)
references
References 37 publications
(66 reference statements)
0
43
0
Order By: Relevance
“…They are normally able to inhibit T- and B-cell proliferation [43], whereas in ITP patients, this property is compromised together with their own proliferation [44,45]. It has been observed that the CB2 receptor is more frequently expressed in healthy MSCs than in MSCs obtained from ITP pediatric patients [23] and that a selective stimulation of the cannabinoid receptor can restore the immunomodulatory capabilities of MSCs [46]. Another well-reported aspect in the literature is the capability of AEA and 2-AG to modulate the platelets’ function and survival.…”
Section: The Ec System In Immune Thrombocytopeniamentioning
confidence: 99%
“…They are normally able to inhibit T- and B-cell proliferation [43], whereas in ITP patients, this property is compromised together with their own proliferation [44,45]. It has been observed that the CB2 receptor is more frequently expressed in healthy MSCs than in MSCs obtained from ITP pediatric patients [23] and that a selective stimulation of the cannabinoid receptor can restore the immunomodulatory capabilities of MSCs [46]. Another well-reported aspect in the literature is the capability of AEA and 2-AG to modulate the platelets’ function and survival.…”
Section: The Ec System In Immune Thrombocytopeniamentioning
confidence: 99%
“…In particular, mesenchymal stem cells from ITP patients overproduce the pro-inflammatory cytokine IL-6. Regular levels are restored using JWH-133, a selective agonist at CB2 receptors [77]. A proper activation of CB2 receptor reduces the levels of several inflammatory mediators (IL-6, IL-1β and TNF-α) also in animal model of multiple sclerosis [78].…”
Section: Inflammation and Cytokines Productionmentioning
confidence: 99%
“…ITP is characterized by abnormal cytokine secretion, especially by overproduction of pro-inflammatory IL-6 by mesenchymal stem cells. Natural activation of CBR2 or JWH-133 selective agonist implementation reduces IL-6 levels in ITP [ 98 ]. Substitution of glutamine (Q) with arginine (R) at the codon 63 in CBR2 protein changes its polarization and affects receptor–cannabinoid interactions reducing immune modulation function of this receptor [ 99 ].…”
Section: Cannabinoids In Medicinementioning
confidence: 99%